In Search of Christian Theological Research Methodology. (October 2018) - Holmes, Colin; Lindsay, David
The burgeoning methodological literature available for the guidance of researchers caters for a wide range of standpoints, but it ignores perhaps the commonest personal philosophies encountered in the nursing profession, those based on Christianity. Nursing's historical and continuing relationship to Christian faith has been well-documented, and although this is reflected in literature stressing the importance of spiritual care, it has had no discernible impact on nurses' formulations of research methodology. This article outlines the core features of Christian belief and draws out some of their methodological implications for nurse researchers, with a view to initiating a constructive debate from which Christian theological methodologies might be developed.